2008
DOI: 10.3748/wjg.14.5701
|View full text |Cite
|
Sign up to set email alerts
|

Estrogen and progesterone receptor isoforms expression in the stomach of Mongolian gerbils

Abstract: The presence of ER-alpha and PR isoforms in gerbils stomach suggests that E2 and P4 actions in this organ are in part mediated by their nuclear receptors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0
3

Year Published

2009
2009
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 36 publications
1
7
0
3
Order By: Relevance
“…This result is similar to that reported for rats [3,8]. Also, the finding that the expected ERβ PCR product was not satisfactorily generated from reverse transcribed mRNA from the uterus of the Mongolian gerbil is consistent with other work [32]. The low level of ERβ expression in the uterus relative to that of ERα may be due to ERβ not being the dominant ER subtype and therefore not playing significant roles in the uterus.…”
Section: Discussionsupporting
confidence: 81%
“…This result is similar to that reported for rats [3,8]. Also, the finding that the expected ERβ PCR product was not satisfactorily generated from reverse transcribed mRNA from the uterus of the Mongolian gerbil is consistent with other work [32]. The low level of ERβ expression in the uterus relative to that of ERα may be due to ERβ not being the dominant ER subtype and therefore not playing significant roles in the uterus.…”
Section: Discussionsupporting
confidence: 81%
“…MNNG-induced gastric cancers in rats have been described to occur more fre- quently in males than in females (Furukawa et al, 1982), and this also suggested that estrogen may play a suppressive role in gastric carcinogenesis (Campbell-Thompson et al, 1999;Furukawa et al, 1982). Estrogen and ER signaling pathways are implicated to play important roles in several physiologic and pathologic outcomes, especially cell growth and transformation (Brandenberger et al, 1997;Enmark et al, 1997;Furukawa et al, 1982;Muramatsu and Inoue, 2000;Saqui-Salces et al, 2008). Cyclin D1/cdk4 are important target genes through which ERα appears to play a key role in estrogen-provoked cellular proliferation, whereas ERβ inhibits transcription of cyclin D1/cdk4 genes and blocks ERα-mediated induction (Liu et al, 2002;Nair et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…The two PGR isoforms, PGR-A and PGR-B, have different transcriptional activities [Giangrande et al, 2000], due to the presence of an additional activation function domain, AF3, on the longer PGR-B isoform [Saqui-Salces et al, 2008; Schrader and O'Malley, 1972]. Aside from this, both isoforms comprise identical ligand binding and DNA-binding domains [Gellersen et al, 2009; Hager et al, 2000; Mulac-Jericevic and Conneely, 2004].…”
Section: Pgr Regulation Of Transcription In Granulosa Cellsmentioning
confidence: 99%